Investor Intentions for Mutual Fund Investments in India: Extended TPB Approach (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Mutual Funds have been promoted as a  medium for retail investors to get into equity  investments and increase their stock market  participation. With the ease of investing in  small amounts and regular intervals, along  with the advantages of diversification of  risk and professional management of funds,  mutual funds present an attractive avenue of  investment. Still the data from Association  of Mutual Funds in India (AMFI) does not  seem to be reflecting this in terms of growth  in mutual fund investments. There is a need to  analyse the factors influencing an individual  investor’s intentions to invest in mutual funds  so as to understand the reasons behind slow  growth of mutual fund investments in India  and to devise ways to increase the same.  This paper analyses the attitudinal, social  and behavioural control factors influencing  the investor intentions of mutual funds  investments using constructs from an extended  model of Theory of Planned Behaviour.
Keywords: Mutual Funds; Investor Intentions; Theory of Planned Behaviour